4CPS-205 Assessment of the palatability of antibiotic oral suspensions: a literature review. (24th March 2020) - Robert, S; Nisse, YE; Béatrice, D
Abstract : Background and importance: Non-adherence to a full course of antibiotic occurs in approximately 25% of paediatric patients. The child's refusal to take the drug is the second most common reason for non-adherence. Palatability is the third most important antibiotic feature for parents after effectiveness and safety. Aim and objectives: To review the literature for assessments of the palatability of antibiotic oral suspensions to inform physicians in their daily practice and consequently improve adherence. Material and methods: A systematic literature search was conducted in August 2019 in the Pubmed database. A study was eligible for inclusion if it reported an assessment of the palatability of one or more antibiotic suspensions with any assessment scale among adults and/or children. The lowest score was for poor palatability and the highest for excellent palatability. Study characteristics, population demographics and palatability assessments were extracted. For comparison purposes, all results are expressed on a 10 point scale. Averages were calculated for paediatric and adult populations. Results: Ten studies were identified, all blind: 6/10 with children, 3/10 with adults and 1/10 with both. Children were aged 4–12 years. Participants were healthy volunteers except in one study. Fourteen drugs were tested in children and 24 in adults for a total of 27 drugs tested. Visual analogic scale with 5 point facial hedonic scales (4/10), 5 point facial scales (5/10) or 10 point analogue scales (1/10) were used as the assessment tools. The average palatability was <5 for 3/14 and 12/24 drugs in children and adults, respectively. The palatability score was lower in adults than in children, 10 times out of 11. The average difference between the scores for adults and children was 1.1 point/10. Conclusion and relevance: The majority of the most common antibiotics were covered. Differences in assessment of palatability sometimes existed for the same molecule. This may be related to the formulation tested (brand name or generic drugs). A single study allowed a direct comparison between adults and children. Further investigations are needed to determine the factors affecting the palatability of drugs. However, the available palatability assessments can help the physician to choose between several drugs with the same effectiveness and safety to improve compliance. References and/or acknowledgements: No conflict of interest.